Analisis Pengaruh Faktor-Faktor Produksi Usahatani Terhadap Produktivitas Padi Sawah Di Kelurahan Atula Kabupaten Kolaka Timur - Rezky Anugrah; Idrus Salam; La Ode Alwi (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
This research is motivated by the fact that the size of lowland rice productivity depends on the production factors used, including land area, seeds, Phonska fertilizer, urea fertilizer, labor, pesticides and irrigation. Therefore, the purpose of this study was to determine the effect of farming production factors on lowland rice productivity in Atula Village, East Kolaka Regency. The analytical method used in this research is multiple linear regression analysis method. The results showed that simultaneously farming production factors consisting of land area, seeds, phonska fertilizer, urea fertilizer, labor, pesticides, and irrigation had a significant effect on lowland rice productivity with a significance value in the F test of 0.000 which means it is smaller from the set significance level that is 0.05 (5%). and partially the production factors that significantly influence the productivity of lowland rice are land area, phonska fertilizer, urea fertilizer, pesticides and irrigation. While the production factors that do not have a significant effect are the use of seeds and labor.